Invasive Management of Out of Hospital Cardiac Arrest. (September 2019) - Kelly, Erik M.; Pinto, Duane S.
Abstract : Out of hospital cardiac arrest (OHCA) is a major cause of morbidity and mortality worldwide. Clinical decision making is extremely difficult in this understudied patient population with high prevalence of neurological injury and inexorable shock states. As such, there are uncertain benefits from therapies available in the cardiac catheterization laboratory. Fear of futility and public reporting often affects decision making and can result in risk aversion. This review focuses on invasive management in OHCA care, with particular focus on coronary angiography, coronary revascularization, and mechanical support. Guidelines recommend emergency coronary angiography in patients with ST-segment elevations on ECG after OHCA, while the role of coronary angiography in patients without ST-segment elevations is less clear. Similar uncertainty remains in the appropriate revascularization strategy in these patients. As in other areas of cardiology, there is a growing interest in the role of mechanical circulatory support after OHCA, though the available literature shows mixed results. The many uncertainties associated with treating the patient with OHCA highlight the importance of clinical decision support tools and treatment algorithms in the care of this population. This review focuses on invasive management in OHCA care, with particular focus on coronary angiography, coronary revascularization, and mechanical support.